The gilded girl - Colman, Alyssa (Farrar Straus Giroux for Young Readers, 2021)
Heartfelt, fast-paced, and utterly absorbing, The Gilded Girl is Alyssa Colman's sparkling debut novel about determination, spirit, and the magic of friendship. Any child can spark magic, but only the elite are allowed to kindle it. Those denied access to the secrets of the kindling ritual will see their magic snuffed out before their thirteenth birthday. In 1906 New York City, Miss Posterity's Academy for Practical Magic is the best kindling school--and wealthy twelve-year-old Emma Harris is accustomed to the best. But when her father dies, leaving her penniless, Emma is reduced to working off her debts to Miss Posterity alongside Izzy, a headstrong servant girl who refuses to let her magic be snuffed out, even if society dictates she must. Emma and Izzy reluctantly form a pact: If Izzy teaches Emma how to survive as a servant, Emma will reveal to Izzy what she knows about magic. Along the way, they encounter shy libraries, quizzes that literally pop, and talking cats (that is, house dragons). But when another student's kindling goes horribly wrong, Emma, Izzy, and their unexpected new friends embark on a journey to keep magic in the right hands . . . or else there's a risk it will be snuffed out forever.